Implementasi Variabel Makro: Zakat, Infak Dan Shodaqah (Zis) Pada Pelaku Ekonomi Kreatif Makanan Siap Saji Berbasis Singkong - Masyhuri., Masyhuri (Fakultas Ekonomi, UIN Maliki Malang, 2020)
The purpose of this study is the impact of macro variables on zakat, shodaqah and infaq (Zis) on economic growth (aggregate demand; AD). The initial impact is controlled from the macro variables of consumption, investment, savingÂ and government expenditure. This study is included in the basic research category because the level of technological readiness is 3 (three), namely at the laboratory level. Â Analysis tools are carried out using a graphical and mathematical approach. The results showed that Zis has a sectoral impact on economic growth (AD). The consumption, investment, saving, government expenditure and export variables have a positive impact on AD. Likewise Zis role in economic growth is positive. Whereas interest money has a negative impact. Anticipation without using interest money in the economy is done by increasing economic activity through the implementation of 14 sharia transactions. One of them is the application of qardhul-hasan to the creative economy of cassava-based fast food creative, which shows that the acceleration of the value of the currency compared to the future valueÂ can be created at 6.7 % -10% from before. That is why Zis besides having a positive impact on economic growth (AD) also gave birth to blessing as measured through 3 indicators of blessing, namely ni'mah, sa'adah (goodness) and ziyadah (additional).